ENDEMIC SEROPREVALENCE AND FARMER CONTROL MEASURES OF ANTHRAX AMONG RUMINATE ANIMALS IN PAKISTAN - Nageen Sardar; Aftab Ahmad Anjum; Maryam Javed; Saima Ayub; Nadia Mukhtar; Hassan Bin Aslam; Alan J. Wolfe; Daniel S. Schabacker; Sara Forrester; Mark Khemmani; Amin A. Aqel; Muhammad Furqan Shahid; et al. (Journal of Animal and Plant Sciences, 2023)
Anthrax, caused by Bacillus anthracis (B. anthracis), is an important zoonotic disease of livestock that poses a threat to public safety. The present study aimed to determine the seroprevalence of Bacillus anthracis in sheep and cattle in endemic areas (Punjab and Balochistan provinces) of Pakistan by enzyme-linked immunosorbent assay (ELISA). Cross-sectional survey was also done to assess the control measures of the farmers. Out of 401 serum samples from sheep and cattle, a total of 68 (16.9%) samples were seropositive for anti-PA antibodies; seroprevalence of B. anthracis in sheep and cattle was 22.11% (48/217) and 10.86% (20/184), respectively. Seroprevalence was significantly higher (p<0.05) in Baluchistan province (33.3%, 44/132) compared to Punjab province (8.92%, 24/269). Most farmers (65.90%, 29/44) were not disposing carcasses as recommended. Around 77.28%, 17/22 of the veterinary officials reported the non-availability of vaccine against anthrax and 63.63% (14/22) stated the lack of cold chain for the vaccine storage and transportation. We concluded that seroprevalence of B. anthracis in unvaccinated sheep and cattle is evidence that the pathogen is circulating in Baluchistan and Punjab provinces. So must applied an active surveillance and, strengthened veterinary practices vaccination programs to control anthrax outbreaks in endemic areas.
Keywords: Seroprevalence; Bacillus anthracis; Endemic; Anthrax